Pengaruh Gaya Kepemimpinan dan Komitmen OrganisasiTerhadap Kinerja Pegawai Negeri Sipil Fakultas TeknikUniversitas Sebelas Maret Surakartadengan Motivasi Sebagai Pemediasi - Basuki, Rakhmat, Drs.M.Farid Wajdi,M.M.,Ph.D, Dr. Anton Agus Setyawan, M.Si (2016)
This study aims to measure the effect of leadership styles, organizational commitment to the performance of civil servants of the Faculty of Engineering, University of Sebelas March Surakarta with motivation as mediating. The study population are civil servants. The sample is determined by using saturated sample, the respondents all employees as many as 76 people. Methods of data collection used questionnaire technique. Data analysis methods used path analysis method (Path Analysis). From the results of this study concluded that the style of leadership, organizational commitment and motivation of jointly have a significant influence on employee performance. While the results of the t test of leadership style variable result that leadership style has no effect on the motivation and performance of the organization's commitment and motivation. Variabel partially have a significant influence on employee performance. With path analysis regression coefficient values obtained mediate motivation leadership style on employee performance. Motivation also mediate organizational commitment to employee performance Faculty of Engineering, University of Sebelas March Surakarta. Seen coefficient (R Square) we can conclude that the motivation was influenced variable leadership style and organizational commitment of 0.46% while the rest influenced by other factors beyond the variables. Performance is influenced by the motivation of employees by 44% and the rest influenced by other factors beyond the variables. Performance of employees affected by variables of leadership style and organizational commitment by 36%, while 64% are other variables outside the study.